Suspended scattering particles in motion using OCT angiography in branch retinal vein occlusion disease cases with cystoid macular edema - Kwang-Eon Choi (Nature Portfolio, 2020)
Abstract We aimed to investigate the clinical implication of suspended scattering particles in motion (SSPiM) using optical coherence tomography angiography (OCTA) among branch retinal vein occlusion disease (BRVO) cases with macular edema (ME). Medical records of BRVO patients were reviewed. Central retinal thickness (CRT), ME type, and cyst size on optical coherence tomography images were evaluated before and after intravitreal bevacizumab injection. Nonperfusion area, SSPiM, and microvascular abnormalities in OCTA images were evaluated using a Heidelberg machine. SSPiM was identified in 24 of 56 cases. There were no differences in baseline characteristics between groups with and without SSPiM. Disease duration, disease-free duration, previous injection number, microaneurysms in the superficial vascular complex, and microaneurysms in the deep vascular complex (DVC) (p = 0.003, 0.013, 0.028, 0.003, < 0.001, respectively) differed significantly between the two groups. After multivariate logistic analysis, microaneurysms in the DVC were the only different factor between the two groups (odds ratio [OR]: 0.091; p = 0.001). Furthermore, SSPiM in the DVC (OR 10.908; p = 0.002) and nonperfusion grade (OR 0.039; p < 0.001) were significantly associated with cyst response after intravitreal injection. SSPiM may be correlated with microaneurysms in the DVC and a poor anatomical response after intravitreal injection.